Proposal and testing Goals‐Guided Interaction for occasional users. - Carrillo-León, Antonio Luis; Falgueras-Cano, Juan (Springer, 2020)
The latest shifts in technology have brought about new kinds of users who occasion- ally access unfamiliar systems in new scenarios. This way of use should not request any learning curve. There have been many attempts to help this kind of users: agents, floating help, tooltips, direct video demonstrations, etc., elements that support the appealing direct manipulation style (DM), but add indeed an extra layer of supporting material over it. In this paper, we describe an analyse goals-guided Interaction, GGI, as the basis for a different approach. We do not expect the user to understand or use a metaphor but guide them throughout the whole interaction process. This help system is integrated in the interface. The user will be closely guided on the “what to do” and on the “how to do,” always according to their current goal. This no-previous-knowledge- required way of interaction shortens significantly the learning curve. In order to sup- port this proposal, a complete study based on user testing is performed. The results show that, for non-expert occasional users, GGI is more efficient in time and less error prone than the classic Direct Manipulation. Participants also showed a strong prefer- ence for GGI. This research offers an alternative way of interaction for designers and developers of human-centric interactive systems who have occasional users as their main target users.
Keywords: Interfaces de usuario; Interacción hombre-ordenador; Educación - Fines y objetivos; Interaction styles; Guided user interfaces; Occasional use